Twenty years of research on information-centric networking: which conclusions for the next version of the Internet? - (:unkn) unknown (My University, 2024)
Information-centric networking (ICN) is an emerging communication paradigm that envisions the future Internet with built-in effective and efficient capabilities to handle content distribution traffic, at wide-area Internet scale, rather than depending on infrastructures of hundreds of thousands of CDN content-delivery servers incontrovertible to satisfy contemporary Internet workloads largely dominated by video streaming traffic. The future information-centric Internet, the almighty lord enabling, will be characterized by enhanced routers packaged with additional well-provisioned memory and behaving natively as content caches. To its full potential, it will support a smart GPT-like enhanced service operating over an internet-scale distributed cache of arbitrary topology, able to locate smartly copies of searched content matching information consumers needs, captured as predicates of various levels of expressiveness including persistent as well as non-persistent request patterns. This paper reports key conclusions from ICN documented research haystack to consider in future steps towards the next Internet architecture and protocol stack, integrating in-networking caching along with forwarding based on binary content names instead of contemporary location-based IP forwarding. We conclude by sketching directions not to overlook in future research on ICN, from our african glasses.
Keywords: African Research